1998
DOI: 10.1017/s1357729800010079
|View full text |Cite
|
Sign up to set email alerts
|

Video image analysis for on-line classification of lamb carcasses

Abstract: Video image analysis (VIA), carcass shape and colour data were collected for 1211 lambs of known gender, breed type and carcass weight over a 1-week period using the VIAscan® system developed by the Australian Meat Research Corporation. Classification data (thickness of soft tissue over the 12th rib (GR measurement) and subjective conformation scores on a five-point scale of the leg, loin and shoulder) were assessed by an Agriculture and Agri-Food Canada grader after carcasses had chilled at 5°C for 3 to 6 h. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 13 publications
0
15
0
Order By: Relevance
“…In this study and the studies by Stanford et al (1998), Brady et al (2003) and Rius-Vilarrasa et al (2009), the VIA technology predicted lean meat yield in the leg with the highest accuracy and lean in the loin, with the poorest accuracy of the three primal regions. Stanford et al (1998) did not find any significant VIAscan ® variables to use for predicting lean in the loin and concluded that this was because of the little variation found in this trait.…”
Section: Classification Trialmentioning
confidence: 50%
See 3 more Smart Citations
“…In this study and the studies by Stanford et al (1998), Brady et al (2003) and Rius-Vilarrasa et al (2009), the VIA technology predicted lean meat yield in the leg with the highest accuracy and lean in the loin, with the poorest accuracy of the three primal regions. Stanford et al (1998) did not find any significant VIAscan ® variables to use for predicting lean in the loin and concluded that this was because of the little variation found in this trait.…”
Section: Classification Trialmentioning
confidence: 50%
“…Stanford et al (1998) did not find any significant VIAscan ® variables to use for predicting lean in the loin and concluded that this was because of the little variation found in this trait. The poor performance in predicting lean in the loin in this study could be influenced by the decision to exclude the flanks from the loin, as this reduced the Loin% variability.…”
Section: Classification Trialmentioning
confidence: 97%
See 2 more Smart Citations
“…The most promising and suitable technology developed in recent years is VIA (e.g. Stanford et al, 1998;Hopkins et al, 2004). This provides a non-invasive system operating at normal chain speeds and enables automatic acquisition of data on carcasses from the side and/or back view.…”
Section: Muscle Density and Intramuscular Fat (Imf)mentioning
confidence: 99%